IMPROVING ENGLISH LANGUAGE COMPETENCY IN THE CULINARY SECTOR IN THE SULAMANDU BEACH TOURISM AREA, EAST NUSA TENGGARA: A CASE STUDY OF TRAINING AND IMPACT ON TOURISM SERVICES - O. Manek, Agnes; Isu, Rudolof Jibrael (Media Inovasi Pendidikan dan Publikasi, 2024)
Sulamanda Beach, located in Mata Air Village, Central Kupang Subdistrict, Kupang Regency, East Nusa Tenggara, is one of the leading tourist destinations that offers stunning natural charm and diverse local culinary wealth. To maximize tourism potential and improve the quality of service to tourists, special English language training was conducted for culinary businesses in this area. The training was designed to improve the English language skills of the participants, who consisted of restaurant owners, chefs, and service staff in the culinary sector. The training aimed to evaluate the effectiveness of the English language training in improving participants' language skills as well as its impact on the quality of culinary services provided to tourists. The research methodology included several important steps: first, hands-on practice-based training covering everyday communication situations and customer service scenarios. Second, a pre-test and post-test were conducted. Third, an analysis of feedback from travelers was conducted to measure changes in service quality and customer satisfaction after the implementation of the training. The results of this study are expected to provide in-depth insight into the effect of English language training on improving the communication skills of culinary businesses and its impact on the tourist experience.